The Vital Role Of Branding Design In Enhancing Business Competitiveness And Supporting MSME - Qurotul Aini Nur Salsabila, Arifah; Eka Febiyanti, Latifah; Faturrahman Bataiv, Misbah; Ardya Budiarti, Mukie (LPPM Universitas Duta Bangsa Surakarta, 2023)
This research focuses on micro, small, and medium enterprises (MSMEs) engaged in design and printing services, as economic growth relies heavily on this sector. The study finds that branding, through appealing visual identity, is crucial for establishing emotional connections with consumers, enhancing customer trust, and entering new markets. A case study of the MSME Indiestrustsolo is utilized to illustrate the observation process, results, and discussion. The findings indicate that branding provides a strong foundation for long-term growth. A unique brand identity, through consistent design and active customer interaction, helps build a brand image that is easily recognizable and memorable to consumers. The importance of consistency in brand identity, both visually and in communication style, proves to be a key element in strengthening customer relationships and enhancing brand recall. The methodology employed in this research is qualitative, involving direct observation of the MSME Indiestrustsolo. The study aims to evaluate how branding can influence the competitiveness of MSMEs, particularly in the context of branding design as a key element in marketing products or services. This research demonstrates that effective branding strategies can be the key to MSME success in a dynamic market, enabling them to expand market reach, compete confidently, and achieve long-term success.